2013
DOI: 10.1016/j.icarus.2012.10.019
|View full text |Cite
|
Sign up to set email alerts
|

3D modelling of the early martian climate under a denser CO2 atmosphere: Temperatures and CO2 ice clouds

Abstract: On the basis of geological evidence, it is often stated that the early martian climate was warm enough for liquid water to flow on the surface thanks to the greenhouse effect of a thick atmosphere. We present 3D global climate simulations of the early martian climate performed assuming a faint young sun and a CO 2 atmosphere with surface pressure between 0.1 and 7 bars. The model includes a detailed representation of radiative transfer using revised CO 2 gas collision induced absorption properties, and a param… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
378
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 289 publications
(392 citation statements)
references
References 115 publications
(140 reference statements)
14
378
0
Order By: Relevance
“…However, Sotin et al (2007) found that ocean planets are likely to have a high pressure ice layer between the liquid water ocean and the silicate mantle. Therefore, Lammer et al (2009) classified the ocean planets as class IV habitats, the lowest class of potentially habitable worlds (see also Forget et al 2013). However, Léger et al (2004) and Forget et al (2013) both highlighted the possibility of enriching the ocean with minerals from meteoritic impacts, showing that these planetary objects should not be discarded as potential life habitats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Sotin et al (2007) found that ocean planets are likely to have a high pressure ice layer between the liquid water ocean and the silicate mantle. Therefore, Lammer et al (2009) classified the ocean planets as class IV habitats, the lowest class of potentially habitable worlds (see also Forget et al 2013). However, Léger et al (2004) and Forget et al (2013) both highlighted the possibility of enriching the ocean with minerals from meteoritic impacts, showing that these planetary objects should not be discarded as potential life habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Lammer et al (2009) classified the ocean planets as class IV habitats, the lowest class of potentially habitable worlds (see also Forget et al 2013). However, Léger et al (2004) and Forget et al (2013) both highlighted the possibility of enriching the ocean with minerals from meteoritic impacts, showing that these planetary objects should not be discarded as potential life habitats. In addition, some other mechanisms were put forward to bring minerals to the liquid water layer, such as solid convection (e.g., the presence of 36 Ar at the surface of Titan could be explained by solid convection within the subsurface high pressure ice layer; Niemann et al 2010;Tobie et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…To date no 3-D simulations have calculated the maximum CO 2 greenhouse limit. However, several 3D studies have explored paleo-Earth, paleo-Mars, and high-CO 2 exoplanets scenarios, which may serve as useful steps towards determining the outer edge of the habitable zone around different stars (Wordsworth et al 2011;Urata & Toon, 2013;Forget et al 2013;Wordsworth et al 2013;Shields et al 2016). Several of these data points are included on Fig.…”
Section: Viewed In This Fashion It Is Clear That Lower Effective Tempmentioning
confidence: 99%
“…Investigation of possible structures of circulation fields and properties of clouds in such an atmosphere, especially a dense CO 2 atmosphere, is not only interesting as a problem of fluid mechanics, but also as an important target of research on the early Mars, where the scattering greenhouse effect of CO 2 ice cloud could have played an indispensable role in maintaining possible warm climate (Forget and Pierrehumbert 1997;Mischna et al 2000;Colaprete and Toon 2003;Mitsuda 2007;Forget et al 2013). Previous studies have shown that the intensity of scattering greenhouse effect depends on a number of cloud properties, such as the size distribution of cloud particles, optical depth, cloud cover, and cloud height (Forget and Pierrehumbert 1997;Mischna et al 2000;Kitzmann et al 2013). For the advancement of our understanding on the early Martian climate, it is, therefore, valuable to investigate possible properties of CO 2 clouds consistent with circulation fields of convection associated with condensation of the major atmospheric constituent.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous studies employing one-dimensional models, distributions of cloud particles are specified irrelevant to flow fields. Forget and Pierrehumbert (1997) and Mischna et al (2000), for instance, assume that clouds are localized at specified vertical levels in the condensation layer. Mitsuda (2007) determines the equilibrium distribution of cloud condensates by the local radiative balance, neglecting possible contributions of atmospheric motion and latent heating.…”
Section: Introductionmentioning
confidence: 99%